If (y+3)(y-1) – (y-2)(y-1) = r(y-1), what is the value of y?
(1) r^2 = 25
(2) r = 5
i read a couple explanations on here that i didn't understand, like:
"(y+3)(y-1) – (y-2)(y-1) = r(y-1)
r=5 satisfied both conditions. " E
"5(y-1)=5(y-1) ==> y can be any number.
we found that: r(y-1)=5(y-1).
(1) r=+/- 5
if r=-5 -> y=1
if r=5 -> y= any number ==> we need one value only. Insuff.
(2) r=5 -> y= any number ==> we need one value only. Insuff. " E
but they don't make sense...
the equality itself says that r=5. does this information help us find y? no.
let's see what 1 and 2 tell us.
1. r can be +-5, but we don't care about that, do you agree?
2. r=5. once again, we only have a repetition of what is stated in the text.
neither 1 nor 2 help find y. y can be any value. let's try:
y=1 and r=5:
we have 0=0 so it's ok
let's try with 2, same thing
let's try with 3: we find always r=5.
is that a good explanation?